Implementasi Pengadaan Barang dan Jasa Secara Elektronik dalam Meminimalisir Terjadinya Fraud: Studi Kasus pada Unit Kerja Pengadaan Barang dan Jasa Pemko Sibolga - Nelly Natalia Purba; Deliana; Meily Surianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to see how much benefit there is from implementing the procurement of goods and services before and after the implementation of e-procurement, so that it can minimize things that are indications of fraud. According to Adi, Ardiyani and Ardianingsih (2016) fraud is an act that is contrary to the law and is carried out by internal or external parties of the organization, which aims to gain profit and can cause losses to other parties. This research uses a qualitative method with a descriptive method, where the data collection techniques come from documentation, interviews, literature review, and observations and case studies conducted at the city government's Goods and Services Procurement work unit (UKPBJ). This research focuses on the tender procurement of goods and services with a budget ceiling of more than 200 million using Crowe's fraud pentagon theory, namely arrogance and competence. The results of this analysis show that electronic procurement of goods and services is much more effective in minimizing the occurrence of fraud. The limitation of this research is that e-procurement only covers the selection of goods/services providers, and does not cover the entire goods/services procurement process.